Clinical, Biological, Radiological Pathological and Immediate Post-Operative Remission of Sparsely and Densely Granulated Corticotroph Pituitary Tumors: A Retrospective Study of a Cohort of 277 Patients With Cushing’s Disease - Rak, Beata; Maksymowicz, Maria; Pękul, Monika; Zieliński, Grzegorz (Frontiers in Endocrinology, 2021)
Cushing’s disease is the most common cause of endogenous hypercortisolemia due to a corticotroph pituitary tumor. Up-to-date there is no reliable biomarker of invasiveness among corticotroph tumors, while it is well established in the literature that sparsely granulated somatotroph tumors are characterized by poorer prognosis. The aim of the study was to correlate multiple data including clinical, biochemical, radiological, and pathological findings (including granulation pattern) as well as immediate post-operative remission status among patients operated on due to corticotroph tumors. We enrolled all patients consecutively operated on for planned transsphenoidal neurosurgery due to corticotroph PitNETs in years 2010-2018. We excluded from analysis silent corticotroph tumors, plurihormonal PitNETs, and the Crooke’s cell adenomas. We recorded 348 hormonally active corticotroph PitNETs. The results of the analysis showed the female predominance 79.88% (n=278), with the mean age of Cushing’s disease occurrence 43.27 years of age. The mean time from the first signs and symptoms to the operation was 2 years. The women were diagnosed earlier (20-40 years of age vs. 50-60 years of age among men). We performed a detailed analysis of 277 cases classified by granularity pattern as DG or SG corticotroph PitNETs. Densely granulated tumors (DG) occurred 4 times more frequently than sparsely granulated (SG) (n=225 vs. n=52), at a similar age (mean 42.94; median 40 vs. mean 45.46; median 45.5; p=0.3896),bbut were characterized by lower Knosp’s scale grades (p=0.0147*), smaller preoperative tumors’ volumes measured at MRI, and more commonly exhibited lower Ki-67 labeling index (<3%) (p=0.0168*). What is more, DG adenomas more frequently achieved an immediate remission status (measured as postoperative cortisol concentration <2 µg/dL; p=0.0180*), and the mean postoperative cortisol concentration in DG group was lower than in SG group (mean 5,375 µg/dL vs. 10,47 µg/dL; median 2.49 µg/dL vs. 6.52 µg/dL; p=0.0028**). Our study indicates that DG corticotroph adenomas occurred at a younger age, more commonly were microadenomas as compared to SG tumors, less frequently had invasive features in comparison to SG corticotroph adenomas (p=0.0019**), and more commonly achieved an immediate postsurgical hormonal remission (p=0.0180*).